Towards a socialism of distances? Idiorhythmias and Social Planning between Rossi-Landi and Barthes - Borrelli, Giorgio (E|C, 2024)
In this article, I will propose a dialogue between Ferruccio Rossi-Landi and Roland Barthes. Focusing on the relationship between the individual and society, the Barthesian concept of “diet” – understood as a “life regime” – will be analyzed considering Rossi-Landi’s concept of “programme” – understood as “organized semiosis”. This parallel will be further developed through a comparison between Barthes’ concept of “rhythm” – understood as moving form – and Rossi-Landi’s concept of “social reproduction” – i.e., the developing form of any society. In his course Comment vivre ensemble (1977-1978), Barthes proposed considering Idiorhythmy as the basis for a utopian socialism of distance. Building on this idea, I will try to read Idiorhythmy as a social form based on a disinterested relationship with the other, i.e., as a social form based on Rossi-Landi’s concept of “excess” [eccedenza], which is the human capacity to transcend social programming by creating new forms of semiosis.